PERANAN LINGKUNGAN KERJA TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PT X (PERSERO) FUEL RETAIL MARKETING REGION II PALEMBANG - Muhammad Deni (STIE DWI SAKTI BATURAJA, 2013)
The purpose of this research is to analyze how the working environment at PT. X (Persero) Fuel Retail Marketing Region II does to increase employee productivity. This Analysis was conducted with 7 environmental determinants of physical working that is lighting, colour, air, noise, hygiene and safety security procedures of non-physical environmental factors combined performance of employees based on achievement employees achievement PT. X. This research based on the primary data collection which used questionnaires by 10 respondents employees PT. X. The result of this research, concluded that the physical and nonphysical work environment and the supporting factor has an important role to the increased employee productivity by a factor of job security is assured as the main physical work environment factors that support increased employee productivity.